2013
DOI: 10.1002/mnfr.201300650
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term commercial cow's milk consumption and its effects on metabolic parameters associated with obesity in young mice

Abstract: Whole-milk consumption leads to increased body weight and caloric intake and reduced insulin signaling in WAT, as opposed to low-fat milk consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…Milk intake may reduce the risk of cognitive impairment via modifying neurovascular dysfunction, reducing weight and metabolic risks [32,33]. Animal studies also reported the effect of dairy products in anti-obesity [34,35]. Although no evidence from randomized controlled trials has investigated the preventive effect of milk consumption on cognitive disorders, several trials which showed the protective effect of milk intake against hypertension and obesity might partially support our finding [36,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Milk intake may reduce the risk of cognitive impairment via modifying neurovascular dysfunction, reducing weight and metabolic risks [32,33]. Animal studies also reported the effect of dairy products in anti-obesity [34,35]. Although no evidence from randomized controlled trials has investigated the preventive effect of milk consumption on cognitive disorders, several trials which showed the protective effect of milk intake against hypertension and obesity might partially support our finding [36,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the LF group exhibited a substantial lower liquid consumption and BCAA‐intake compared to the WM group. The lower BCAA‐uptake by the LF group is supported by the measurement of lower BCAA levels in the liver of the LF group animals compared to the hepatic BCAA concentration of mice of the WM group . Accordingly, a higher BCAA‐mediated activation of mTORC1 would explain a higher rate of S6K1 phosphorylation as detected in the liver and WAT of mice of the WM group .…”
mentioning
confidence: 76%
“…Serum, liver, and white adipose tissue (WAT) were tested for parameters associated with obesity and insulin signal transduction. The authors clearly demonstrated that whole milk (WM) consumption leads to increased body weight and caloric intake and reduced insulin signaling in WAT . In comparison to the WM group, consumption of low fat (LF) milk resulted in less weight gain and less phosphorylation of the mTORC1 substrate S6K1 indicating reduced mTORC1‐sigaling and attenuated S6K1‐induced insulin resistance (Fig.…”
mentioning
confidence: 96%
See 2 more Smart Citations